1999
DOI: 10.1080/000155599750011354
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma-related Antigen (SCCr-Ag), sICAM-1 and β2-Microglobulin are Useful Markers of Disease Activity in Psoriasis

Abstract: Several published studies suggest the involvement of immune and inflammatory factors in psoriasis. We recently demonstrated that the number of circulating ICAM-1 + lymphocytes and the levels beta 2-microglobulin are useful parameters in monitoring the activity of the disease. In this study we investigated serum levels of SCCr-Ag in 24 patients with psoriasis in order to determine whether this antigen is a marker of disease activity. Our results demonstrated high serum levels of SCCr-Ag, IL-2, sIL-2R, sCD4, sCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In addition, upregulation of SERPINB3 is associated with benign hyperplasia [ 32 ]. SERPINB3 is highly expressed in psoriasis [ 33 ], cutaneous SCC [ 34 ], and all SCC specimens as well as psoriasis [ 32 ]. In our predictions, we found that SERPINB3 is associated with malignant tumors of the cervix and malignant neoplasms of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, upregulation of SERPINB3 is associated with benign hyperplasia [ 32 ]. SERPINB3 is highly expressed in psoriasis [ 33 ], cutaneous SCC [ 34 ], and all SCC specimens as well as psoriasis [ 32 ]. In our predictions, we found that SERPINB3 is associated with malignant tumors of the cervix and malignant neoplasms of the skin.…”
Section: Resultsmentioning
confidence: 99%